Influence of texture on tyre road noise spectra in rubberized pavements. (February 2020) - Del Pizzo, Alessandro; Teti, Luca; Moro, Antonino; Bianco, Francesco; Fredianelli, Luca; Licitra, Gaetano
Graphical abstract: Abstract: Road traffic noise is the most common source of environmental pollution in urban areas and therefore, the study of noise mitigation actions is fundamental for urban planning. The main source of road traffic noise is tyre/road interaction; thus, the use of low noise road surfaces represents an optimal solution for its mitigation. Several studies tried to find a correlation between road texture and broadband noise data, trying to provide guidelines for the development of acoustically optimised road surfaces. The present work studies the correlation between road texture and tyre/road noise from an experimental point of view, by analysing texture and noise spectra on ten different road surfaces. Tyre deformation has also been addressed by analysing two already existing tyre envelopment algorithms. The first algorithm, proposed by Von Meier and based on the limitation of the second order derivative of the profile signal, shows poor correlation with high frequency noise, while the second algorithm, based on a novel method proposed by Sandberg and Goubert and called indenter method, enhances correlation with low frequency noise and preserves information at higher frequencies. Correlation patterns show that rolling noise can be separated in three main contributions: low, middle and high frequency noise. Finally, experimental tyre/road noise and enveloped texture data obtained with the indenter algorithm have been used to elaborate a linear model that relates low and high frequency noise to texture one-third octave bands. This model deepens knowledge on tyre/road interaction.